Descriptive and quantitative analysis of fracture systems in a carbonate rock mass complex. Issue 1 (August 2021) - Gallas, J; Backers, T
Abstract: The study area is located in the Franconian Alb in Southern Germany and is an Upper Jurassic, karstified and fractured, regularly bedded carbonate rock mass with thin marl interlayers. Structurally, these deposits are heterogeneous and a classification into structural types is striven for in this study. The structural classification is based on discontinuity and fault characteristics gained from field work. The study area is considered an analogue for Germanys most productive deep geothermal reservoir horizon in the South German Molasse Basin. The aim of the field study is to describe and quantitatively analyse the different structural types, and to optimize the scanline method for a specific geological setting to gain comprehensive information with regard to fracture permeability and rock mass behaviour. The structural types are described in terms of discontinuity orientation and density, rock strength, and fault characteristics. To optimize the scanline method for the field study additional discontinuity attributes were added. One of these accessory attributes, the existence of discontinuity lags, will be discussed. It occurs when vertical and sub-vertical fractures cross sedimentary layers and continue with a small horizontal displacement in the next sedimentary layer. The results of this study are used to improve derived fracture networks with respect to thermo-hydro-mechanical models in the geothermal sector. Following article discusses the first results of the above-mentioned field study.